EXAMINING THE IMPACT OF HUMAN RESOURCE MANAGEMENT PRACTICES ON JOB SATISFACTION AMONG OPERATIONAL-LEVEL EMPLOYEES IN THE GARMENT INDUSTRY: EVIDENCE FROM DHAKA, BANGLADESH - Rupa, Mst Fahmida Khatun; Swee, Darian Low Eng (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This research investigates the relationship between Human Resource Management (HRM) practices and job satisfaction among operational employees in the garment industry of Dhaka, Bangladesh. Grounded in Social Exchange Theory, the study examines how supportive HRM practices foster positive employee attitudes and enhance job satisfaction. The HRM practices examined include training and development, employee involvement and participation, and performance appraisal. Considering the garment industry’s crucial role in Bangladesh’s economy, understanding the impact of these practices on employee satisfaction is vital for boosting workforce efficiency and organizational performance. A quantitative research design was adopted, using a structured questionnaire to collect data from 384 employees selected through simple random sampling. The findings reveal that employee involvement and participation (β = 0.377, p < 0.001) is the strongest predictor of job satisfaction, followed by performance appraisal (β = 0.160, p = 0.001). In contrast, training and development (β = −0.135, p = 0.003) shows a small but significant negative association, suggesting that current training programs may not fully align with employee expectations or perceived usefulness. These results underscore the importance of participatory management and equitable performance evaluation systems in promoting employee satisfaction and commitment. The study contributes to HRM literature in emerging economies by identifying participatory management and fair performance appraisal practices as the most influential predictors of job satisfaction among operational garment workers, providing actionable insights for HR managers and policymakers to enhance employee involvement and organizational performance.